Hallmarks of cancer drug resistance and overcoming ways: a paradigm - Islam, Muhammad Torequl (International Journal of Pharmaceutical & Biological Archive, 2018)
Over 100 types of cancers, affecting humans still remain most fearful disease in the world. To date, a number of anticancer therapies have been introduced. However, resistance in cancer is a running matter. This review focuses to seek out possible pathways of cancer resistance, ways of overcoming resistance and still remaining challenges to be resolved. The ways concerning cancer resistance are: cross resistance, resistance-promoting adaptive responses, tumor microenvironment, drug detoxification and inactivation, decreased drug accumulation, alterations in drug targets, drug efflux and compartmentalization, altered cell cycle events, alteration in apoptosis, autophagy, angiogenesis and proliferation, DNA damage repair, alterations in membrane lipids, resistance mutations, cancer stem cells and epigenetics. Along with host factors, some other factors such as p53, Pgp, MRP family, BCRP, LRP, sphingosine 1-phosphate, glucosylceramide, Bcl-2 family genes and PTEN also have contributions in anticancer drug resistance. MDR, MDR modulators, multifunctional nanoparticles, iRNA interference, targeted therapy, adaptive immunotherapy, or combination therapies are useful to overcome a number of cancer resistance. However, inevitable recurrences, cancer progression and metastasis along with the efficacy, safety, inherited/ acquired drug resistance, incomplete elucidation of anticancer drug resistance and the host factors are still-remained challenges in cancer therapy.